Surgical results of orbital decompression: Comparing the removal of the inferomedial and superolateral orbital walls - Andrei Koerbel; André Eduardo de Almeida Franzoi; Jéssica Jacques Berger; Eduardo Wollmann; Helena Bedatti Zeh; Augusto Radunz Amaral; Veralucia Ferreira Oliveira; Debora Raquel Rigon Narciso Fachin (Interdisciplinary Neurosurgery, 2023)
Objective: Orbital decompression aims to control ocular proptosis, the most commonly associated sign in Graves’ disease, and enable ocular rehabilitation. While various surgical approaches have been studied separately, no studies have compared them. This study compared the functional results of two surgical approaches for the treatment of ocular proptosis secondary to Graves’ disease, namely orbital decompression achieved by inferomedial versus superolateral wall removal. Methods: This study included 39 patients who underwent orbital decompression due to Graves’ disease. Twenty-four decompressions were performed by removing the inferomedial orbital walls using an endoscopic endonasal approach. Fifteen decompressions were completed by removing the superolateral orbital walls using a frontolateral approach. T-tests were used to compare means, whereas Fisher’s exact test and the chi-square test were used to compare proportions. Results: Patients who underwent inferomedial orbital decompression presented a higher risk of new-onset strabismus/diplopia (16.7%) than those who underwent decompression via the frontolateral approach (0%). Although no cases of preoperative strabismus worsened after superolateral decompression, all cases of preoperative strabismus worsened after inferomedial decompression. Conclusions: Both approaches achieve a reasonable decompression limit. Superolateral orbital decompression tended to offer better outcomes for diplopia and strabismus than inferomedial decompression. Due to the high risk of worsening strabismus and diplopia in patients presenting with these symptoms preoperatively, they should be treated with the transcranial approach whenever possible.